Changes in quality of care and costs induced by implementation of a diabetes program in a social security entity of Argentina - González L; Elgart JF; Calvo H; Gagliardino JJ (Dove Medical Press, 2013)
Lorena González,1 Jorge F Elgart,1 Héctor Calvo,2 Juan J Gagliardino11Center of Experimental and Applied Endocrinology, National University of La Plata, La Plata, Argentina; 2School of Economics and Management of Healthcare Organizations, National University of La Plata, La Plata, ArgentinaPurpose: To measure the impact of a diabetes and cardiovascular risk factors program implemented in a social security institution upon short- and long-term clinical/metabolic outcomes and costs of care.Methods: Observational longitudinal cohort analysis of clinical/metabolic data and resource use of 300 adult male and female program participants with diabetes before (baseline) and 1 and 3 years after implementation of the program. Data were obtained from clinical records (Qualidiab) and the administration's database.Results: The implementation of the program in "real world" conditions resulted in an immediate and sustainable improvement of the quality of care provided to people with diabetes incorporated therein. We also recorded a more appropriate oral therapy prescription for hyperglycemia and cardiovascular risk factors (CVRFs), as well as a decrease of events related to chronic complications. This improvement was associated with an increased use of diagnostic and therapeutic resources, particularly those related to pharmacy prescriptions, not specifically used for the control of hyperglycemia and other CVRFs.Conclusion: The implementation of a diabetes program in real-world conditions results in a significant short- and long-term improvement of the quality of care provided to people with diabetes and other CVRFs, but simultaneously increased the use of resources and the cost of diagnostic and therapeutic practices. Since controlled studies have shown improvement in quality of care without increasing costs, our results suggest the need to include management-control strategies in these programs for appropriate medical and administrative feedback to ensure the simultaneous improvement of clinical outcomes and optimization of the use of resources.Keywords: management, program evaluation, chronic diseases, diabetes